Cortical and thalamic innervation of the striatum - Doig, N; Natalie Doig (2012)
The basal ganglia are a collection of sub-cortical nuclei involved in the execution of a range of motor and cognitive behaviours. The striatum is the input nucleus of the basal ganglia, receiving major excitatory innervation from the cerebral cortex and intralaminar thalamic nuclei. The main target of these two pathways are the principal striatal neurons, the medium-sized spiny neurons (MSNs), which are subdivided based on their axonal targets and the expression of molecular markers. Direct pathway neurons project to the output nuclei of the basal ganglia and express the D dopamine receptor subtype, whereas indirect pathway MSNs project to the output nuclei via the globus pallidus, and express the D receptor. The striatum also contains interneurons that are essential in processing information within striatum; the cholinergic interneuron is of particular interest due to its role in reward-related behaviour. The aim of this study was to examine the cortical and thalamic innervation of subtypes of striatal neurons. To examine whether the cortical or thalamic afferents selectively innervate direct or indirect pathway neurons, transgenic mice expressing GFP under either the D or D receptor promoter were used. Striatal sections from these mice were immunostained to reveal the GFP and selective markers of the cortical and thalamic afferents, VGluT1 and VGluT2, respectively. A quantitative electron microscopic examination of synaptic connectivity was carried out. The results indicate that there is no selectivity of either the cortical or thalamic pathway for D or D expressing MSNs. Thus both direct and indirect pathway MSNs are involved in the processing of both cortical and thalamic information. The cortical and thalamic innervation to cholinergic interneurons was also examined. Stimulation of cortex and thalamus in vivo in anaesthetised rats resulted in short-latency excitatory responses in identified cholinergic interneurons, indicative of monosynaptic connections. After recording, cholinergic interneurons were filled with neurobiotin. The synaptic innervation from cortex and thalamus was then examined in two individual, electrophysiologically characterised, and neurochemically identified cholinergic interneurons. One neuron received input from both cortex and thalamus, whereas the other neuron received input from the thalamus only. These results provide anatomical and physiological data illustrating how the excitatory inputs to striatum innervate cholinergic interneurons.